Menstimulasi Para Ibu Anggota Kelompok Pengajian Menjadi Startup - Shofia Amin; Rike Setiawati; Fitri Widiastuti; Mulyadi Raf; Asep Machpudin (Jurnal Surya Masyarakat, 2021)
Becoming a startup for mothers who are members of the recitation group is an effort to increase family income. However, if we don't have the courage to start a business, all of our wishes will just become a dream that won't come true. This service activity aims to stimulate courage and change the mindset of the women of the Raudhatul Jannah recitation group, Koto Rendah Village, Siulak District, Kerinci Jambi Regency to develop her potential from being a housewife who has daily gardening activities, becoming a startup by synergizing with her group members. Through the counseling and discussion method, how to start a startup business, determinants of startup success, the role of technology in business and opening access to online-based sales are given to them. The result achieved is the formation of a Joint Business Group (KUBE) which consists of similar business groups and collaborates in running businesses in groups.